2020
DOI: 10.3390/cells10010035
|View full text |Cite
|
Sign up to set email alerts
|

Novel Interplay between p53 and HO-1 in Embryonic Stem Cells

Abstract: Stem cells genome safeguarding requires strict oxidative stress control. Heme oxygenase-1 (HO-1) and p53 are relevant components of the cellular defense system. p53 controls cellular response to multiple types of harmful stimulus, including oxidative stress. Otherwise, besides having a protective role, HO-1 is also involved in embryo development and in embryonic stem (ES) cells differentiation. Although both proteins have been extensively studied, little is known about their relationship in stem cells. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 88 publications
1
8
0
Order By: Relevance
“…On the other hand, the increase in its expression during differentiation and our finding that it is repressed by OCT4, whose levels and function decrease along differentiation, reinforce the hypothesis that HO‐1 might be relevant for this process. We have previously performed a bioinformatic analysis with public data from high‐throughput microarrays and RNA‐sequencing experiments and found that HO‐1 mRNA levels increase in nondirected and in multiple different types of directed differentiation protocols; however, we have also found that HO‐1 mRNA levels decrease in differentiation directed to the endodermal lineage [62]. This is consistent with the fact that basal HO‐1 expression is high in some cellular types and low in others [62,63].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, the increase in its expression during differentiation and our finding that it is repressed by OCT4, whose levels and function decrease along differentiation, reinforce the hypothesis that HO‐1 might be relevant for this process. We have previously performed a bioinformatic analysis with public data from high‐throughput microarrays and RNA‐sequencing experiments and found that HO‐1 mRNA levels increase in nondirected and in multiple different types of directed differentiation protocols; however, we have also found that HO‐1 mRNA levels decrease in differentiation directed to the endodermal lineage [62]. This is consistent with the fact that basal HO‐1 expression is high in some cellular types and low in others [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously performed a bioinformatic analysis with public data from high‐throughput microarrays and RNA‐sequencing experiments and found that HO‐1 mRNA levels increase in nondirected and in multiple different types of directed differentiation protocols; however, we have also found that HO‐1 mRNA levels decrease in differentiation directed to the endodermal lineage [62]. This is consistent with the fact that basal HO‐1 expression is high in some cellular types and low in others [62,63]. It is worth mentioning that, in this work, we have analyzed an early time point of a nondirected differentiation protocol that displays a relatively homogeneous cell population in which there are no terminally differentiated cells yet.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations